Economic recession and infrastructural development in Ikare, Akoko, Ondo State, Nigeria: What implications? - Adejompo Fagbohunka (Economic and Environmental Studies (E&ES), 2018)
This paper investigates the implication of economic recession on the infrastructural development using Ikare, Akoko, Ondo state as a case study. The study posits that infrastructural facilities are a potent indicator of socio-economic performance of a region and could be understood from the perspective of economic recession, which undoubtedly affects and determines both the welfare, advancement, economy and political sphere of a region. The first stage in the collection of primary data was the reconnaissance survey of eleven wards of the city. Fifteen copies of the questionnaire were administered in each ward, making a total of one hundred and sixty-five questionnaires; on the whole, 153 questionnaires were retrieved for the analysis. The study also adopted secondary sources of data and analyzed them both descriptively and inferentially. The research revealed that economic recession had impacted negatively on access to power supply, transportation and health status of the respondents. Furthermore, the paper found out that economic recession had an unpleasant effect on the housing and educational facilities in the study area. Moreover, the research showed an unpronounced effect of the economic recession on portable water supply and telecommunication of the respondents. The Chi-Square test carried on the effect of economic recession on infrastructural facilities, revealed the calculated value 48, while the tabulated Chi-Square value is 0.1036. This shows that economic recession makes significant impacts on the infrastructural facilities of Ikare Akoko, Ondo State. Also, it was vivid from the research that the government's efforts to alleviate the problems of economic recession on infrastructural facilities are commendable. The paper recommends more tripartite governmental investment at local, state and federal levels in the infrastructural sector of the economy, also, the existing infrastructure should be adequately maintained by the concerted efforts of the populace and governments.
Keywords: H54; F63; F64; Q56; Q58; 330; economic recession; infrastructural facilities; development; Ikare Akoko